Acetyl-L-Carnitine and Nicotinamide for Prevention of Type 1Diabetes I-Literature Rewiew Which Gave Support to the Treatment. II-Case Report, Evaluation of Five Years Treatment - Fernandez, Ivana (2015)
n the first part, this article review the accepted knowledge of type 1 diabetes, its physiopathology, the importance of cytokines and the induction of apoptosis and necrosis during its evolution. Throughout this work we describe in more detail the inhibition of this mechanism of cell destruction by acetyl-L-carnitine and nicotinamide. We also explain the complementary action of their association which gave support to the treatment. In the second part, we present the complete evolution of 8 children treated with the oral medication of 50 mg/Kg of acetyl-L-carnitine plus 25 mg/Kg of nicotinamide during 5 years. We published the first 2 years of evolution under treatment in these children (JPEM 26: 347, 2013). The children had positive auto-antibodies and were consanguineous of type 1 diabetic patients. The intravenous glucose tolerance test (IVGTT) showed a first phase of insulin release minor of 48 μU to enter in the protocol, and the same test was used for children evolution. Seven out eight children stopped the treatment because they normalized the metabolic parameters and no one became diabetic. All children increased the insulin response to IVGTT (between 1.44 to 5.69 times). Along the treatment, seven of these eight children turned their positive auto-antibodies into negatives.